KEBIJAKAN DIVIDEN PERUSAHAAN ENERGI: CORPORATE GOVERNANCE, PROFITABILITAS - Oktananda, M. Reza; Sinta, Dwi (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2025)
This study examines the factors that influence dividend policy in energy companies listed in Indonesia during the 2019 – 2023 period. Dividend policy plays an important role because it is related to the allocation of profits earned by the company, while also considering the differing interests between managers and shareholders. The purpose of this study is to understand the relationship between board size, board independence, and profitability in relation to dividend policy. The method used in this research is panel data regression analysis to analyze data from listed energy companies. The results show that board size has a negative effect on dividend policy, while profitability, as measured by Return on Assets (ROA), also demonstrates a negative effect. Board independence has no significant impact on dividend policy. These findings contribute to the understanding of dividend policy in the context of energy companies and highlight the importance of corporate governance in dividend-related decision-making.